Unsignalized Intersection Performance Analysis with PKJI 2023 Method - Vemara Marcha Matitaputty; Richrisna Helena Waas; Ardilson Pembuain (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
Congestion is one of the problems often encountered in Ambon City, one of which is at the intersection of four intersections between Jl. Dr. Kayadoe, Jl. Dr. Siwabessy, and Jl. Dr. Sitanala, where at certain times there are often delays and even queues of vehicles because this area includes residential, shopping, office, and educational areas so that the traffic flow is quite busy. This study aims to determine the performance of the four-arm unsignalized intersection using the PKJI 2023 Method, to determine the growth in the number of vehicles in 2043, and to determine the traffic management efforts used to handle intersection conditions. The results of the study showed that the traffic volume was 2,238.20 pcu/hour, the degree of saturation was 0.39 which means it is included in the category of service level B, the intersection delay value was 9.30 sec/vehicle and the queue opportunity value with an upper limit range of 17.94 to a lower limit of 7.14. Meanwhile, the results of motor vehicle projections using the least square method show that the number of motor vehicles in 2043 or the next 20 years will be 969,073 vehicles, so traffic management efforts must be started early considering the projected growth of vehicles which is increasing from year to year.